Is the revised 2018 FIGO staging system for cervical cancer more prognostic than the 2009 FIGO staging system for women previously staged as IB disease?. (September 2019) - Ayhan, Ali; Aslan, Koray; Bulut, Ayça Nazlı; Akilli, Hüseyin; Öz, Murat; Haberal, Ali; Meydanli, Mehmet Mutlu
Abstract: Objective: The purpose of this study was to compare the prognostic value of the revised FIGO staging system with that of the 2009 FIGO staging system for women previously staged as IB disease. Methods: Institutional cervical cancer databases of two high-volume gynecologic cancer centers in Ankara, Turkey, were retrospectively analyzed. Only women with 2009 FIGO stage IB1 or IB2 disease who underwent primary surgery were included. Survival curves were generated using Kaplan-Meier plots, and the log-rank test was used for survival comparisons. The Cox proportional hazards regression model was used to obtain hazard ratios (HRs) and 95% confidence interval (CI). Results: Data from 425 women were analyzed. The 2009 FIGO stage IB2 (n = 131) disease was associated with a nearly three-fold increased risk of mortality when compared to the 2009 FIGO stage IB1 (n = 294) disease (HR: 2.72, 95% CI: 1.69–4.37; p < 0.001). Stage migration was observed in 372 (87.5%) patients, according to the revised FIGO staging system, leading to no significant difference in five-year overall survival rates between stage IB1 (n=53) and IB2 (n=127) disease (95.2% vs. 89.3%, respectively; p = 0.23), or between stage IB2 (n=127) and IB3 (n=95) disease (89.3% vs. 84.2%, respectively; p = 0.12). Similarly, there was no significant difference in five-year overall survival rates between stage IIIC1 (n=114) and IIIC2 (n=36) disease (79.0% vs. 67.2%, respectively; p = 0.34). Conclusion: When compared to the 2009 FIGO staging system, the revised staging system has more sub-stages, which leads to fewer patients in each sub-stage, resulting in diminished statistical power.